2005
DOI: 10.1248/cpb.53.1515
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Evaluation of New Progesterone Esters as 5.ALPHA.-Reductase Inhibitors

Abstract: In this study we report the synthesis and pharmacological evaluation of four new progesterone derivatives; 17alpha-hydroxy-16beta-methylpregna-4,6-diene-3,20-dione 12, 17alpha-cyclopropylcarbonyloxy-16beta-methylpregna-4,6-diene-3,20-dione 13, 17alpha-cyclobutylcarbonyloxy-16beta-methylpregna-4,6-diene-3,20-dione 14, 17alpha-acetoxy-16beta-methylpregna-4,6-diene-3,20-dione 15 and the pregnatriene compound 17alpha-cyclobutylcarbonyloxy-16beta-methylpregna-1,4,6-triene-3,20-dione 16. The pharmacological effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Cabeza et al reported the synthesis and human steroidal 5α-reductase-II inhibitory activities of several series of pregnane derivatives having diversity in structure and potency profile (Figure ). A 3D-QSAR study was reported on a data set of 30 molecules of pregnane series in our laboratory. …”
Section: Results and Discussion Of 3d-qsar Studies On Steroidal 5α-re...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cabeza et al reported the synthesis and human steroidal 5α-reductase-II inhibitory activities of several series of pregnane derivatives having diversity in structure and potency profile (Figure ). A 3D-QSAR study was reported on a data set of 30 molecules of pregnane series in our laboratory. …”
Section: Results and Discussion Of 3d-qsar Studies On Steroidal 5α-re...mentioning
confidence: 99%
“…A wide variety of data sets bearing 4-azasteroids (Finasteride analogues), , 3-carboxysteroids (Epristeride analogues), pregnane scaffold, and 6-azasteroids as potential inhibitors of steroidal 5α-reductase were employed for the present comparative 3D-QSAR studies. Data sets where the inhibitory activities of these compounds were measured by a single protocol and derived from the same laboratory were selected in each study.…”
Section: D-qsar Methodology Employed For Steroidal 5α-reductase Inhib...mentioning
confidence: 99%